2008
DOI: 10.1002/mame.200800080
|View full text |Cite
|
Sign up to set email alerts
|

UV Curing of Organic‐Inorganic Hybrid Coatings Containing Polyhedral Oligomeric Silsesquioxane Blocks

Abstract: Hybrid nanocomposite coatings were prepared by the UV‐curing technique with a methacrylic oligomer and multifunctional methacrylic polyhedral oligomeric silsesquioxane blocks (POSS®). The results obtained from the polyhedral compounds were compared with those of a disordered framework obtained by the condensation of a silica precursor (MEMO). The inorganic domains generated during synthesis created constraints in movement of polymer segments, which reflected in an increase in Tg of the hybrid nanocomposite coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…As an example the RT-FTIR spectra for a methacrylic resin at different irradiation time are shown in Figure 2 [ Amerio et al 2008]. It is evident that the band at 1630 cm -1 (C=C), attributed to the methacrylic functional group, decreases during irradiation of the sample with the UV beam.…”
Section: Real Time Ftir Spectroscopymentioning
confidence: 99%
“…As an example the RT-FTIR spectra for a methacrylic resin at different irradiation time are shown in Figure 2 [ Amerio et al 2008]. It is evident that the band at 1630 cm -1 (C=C), attributed to the methacrylic functional group, decreases during irradiation of the sample with the UV beam.…”
Section: Real Time Ftir Spectroscopymentioning
confidence: 99%
“…In numerous papers they have been utilized to reinforce the matrix structure of a wide range of thermosets and/or thermoplastics. These hybrid materials have been used for improving the surface properties of a typical methacrylic coating (Amerio et al 2008). The final properties of UV cured films demonstrated that introducing 5 and 10 % of POSS content in the organic resin enhanced the scratch resistance around 5 and 8 times, respectively.…”
Section: Reinforcing Fillersmentioning
confidence: 99%
“…This is in agreement with other research reports that using quantitative crosslink agent to epoxy resin UV-curing systems can increase thermal stability. 25,26 In the case of DSC analysis, the DSC curves of the samples are displayed in Fig. 4, and the T g values are indicated by the arrows in this figure and listed in Table 2.…”
Section: Thermal Analysismentioning
confidence: 99%